University teachers’ perceptions of Flipped Learning according to their digital profile (Praxis Educativa, 2026)
The integration of digital technologies into education is a major global challenge, particularly for educators with low levels of digital teaching competence (DTC). To address this, the Flipped Learning (FL) model encourages the use of digital tools and promotes active learning. This qualitative, exploratory, and descriptive study analyzes the perceptions of university professors who have implemented FL. The COMDID-A instrument was used to assess their DTC, and semi-structured interviews were conducted and analyzed through thematic analysis. Although a high level of DTC is helpful, it is not indispensable. Professors used a variety of digital tools but faced challenges such as pedagogical planning and low initial student participation. It is recommended to strengthen institutional support, refine instructional templates, and foster faculty collaboration.
Keywords: Flipped learning; digital teaching competence; higher education; pedagogical innovation; instructional design